Fixing the communication gap through mhealth: The effects of attitude, perceived usefulness, and risks of Mhealth on prescribed self-care among coronary heart disease patients in Malaysia - Abu Seman, Rabiah Adawiah; Md Syed, Md Azalanshah; Aziz, Azmin Azliza; Mahmood Zuhdi, Ahmad Syadi; Mohd Zamin, Rasheeda (Taylor's University College, 2020)
This study analyses the moderating role of Mobile Health (MHealth) in influencing the indirect relationship of health literacy on prescribed self-care through attitude among Coronary Heart Disease (CHD) patients in Malaysia. Through a user-experience research with concept testing, data were collected from 300 CHD patients in a tertiary hospital using a survey. Findings show a partial mediation of attitude in the relationship between health literacy and prescribed self-care. The results reveal that the perceived usefulness of MHealth significantly and positively moderates the direct effect of health literacy on attitude towards prescribed self-care. Further, the perceived risk of MHealth significantly moderates the direct effect of health literacy on prescribed self-care negatively. Lastly, the perceived risk of MHealth positively moderates the moderated mediation of perceived usefulness of MHealth on the indirect effect of health literacy on prescribed self-care. These findings suggest a new framework for the effects of MHealth on prescribed self-care that explains the importance of perceived usefulness of MHealth to create a positive attitude towards prescribed self-care; in other words, the perception of usefulness outweighs the patient’s perceived risk of MHealth in practising prescribed self-care. To integrate MHealth in the CHD medication regimen, requires (1) relevant disease management functions, (2) regulations (3) audit and revisions, and (4) education, as well as the involvement of healthcare providers, policymakers, and developers. © SEARCH Journal 2020.